2000
DOI: 10.1136/jms.7.2.105
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity, specificity, and positive predictive value of screening mammography and symptomatic status

Abstract: Objective-To examine whether the accuracy of screening mammography varies according to symptomatic status reported at the time of screening. Setting-Victoria, Australia, where free biennial screening is provided to women aged 40 and older. Methods-We examined the sensitivity, specificity, and the positive predictive value of screening mammography by symptom status in 106 826 women from Victoria, who attended for first round mammography in 1994 and who did not have a personal history of breast cancer. Symptomat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
7

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 36 publications
1
30
1
7
Order By: Relevance
“…Recall and PPV are known to differ by screening interval and whether a screening mammogram is the initial or a subsequent study. 9,13,14,29 …”
Section: Phase IIImentioning
confidence: 99%
“…Recall and PPV are known to differ by screening interval and whether a screening mammogram is the initial or a subsequent study. 9,13,14,29 …”
Section: Phase IIImentioning
confidence: 99%
“…3,[5][6][7]10 Although screening is typically conducted among asymptomatic women, one study has reported that approximately 10% of women report symptoms at a screening examination. 11 It is not clear how much the presence of symptoms increases the risk of breast cancer at screening exams. This is particularly important because studies have shown that the specificity of screening and diagnostic exams may be lower for women with breast symptoms compared with women without symptoms.…”
mentioning
confidence: 99%
“…The trade- Table 1: Results of mammogram (Mx) and ultrasound (US) screening from the parallel assessment study of Houssami et al [16] and mammogram baseline data from Kavanagh et al [17].…”
Section: Believe the Positive Protocolmentioning
confidence: 99%
“…The MLEs of the sensitivity and specificity of the believe the negative protocol and of the log-ratios of the likelihood ratios are obtained by substituting the MLEs given in Equation (20) into Equations (16)(17)(18)(19).…”
Section: Analysis For the Believe The Negative Protocolmentioning
confidence: 99%
See 1 more Smart Citation